Printed Thermoelectrics. Issue 18 (23rd March 2022) - Burton, Matthew; Howells, Geraint; Atoyo, Jonathan; Carnie, Matthew
Abstract: The looming impact of climate change and the diminishing supply of fossil fuels both highlight the need for a transition to more sustainable energy sources. While solar and wind can produce much of the energy needed, to meet all our energy demands there is a need for a diverse sustainable energy generation mix. Thermoelectrics can play a vital role in this, by harvesting otherwise wasted heat energy and converting it into useful electrical energy. While efficient thermoelectric materials have been known since the 1950s, thermoelectrics have not been utilized beyond a few niche applications. This can in part be attributed to the high cost of manufacturing and the geometrical restraints of current commercial manufacturing techniques. Printing offers a potential route to manufacture thermoelectric materials at a lower price point and allows for the fabrication of generators that are custom built to meet the waste heat source requirements. This review details the significant progress that has been made in recent years in printing of thermoelectric materials in all thermoelectric material groups and printing methods, and highlights very recent publications that show printing can now offer comparable performance to commercially manufactured thermoelectric materials. Abstract : Thermoelectrics turns wasted heat energy into useful electrical energy. Current commercial manufacturing techniques are time and energy intensive, contributing to low utilization of thermoelectrics. This review explores how printing has been used to make thermoelectric materials and generators, and how advances in the last five years hold great promise for printing to become the dominant future manufacturing technique for thermoelectrics.